2022
DOI: 10.1038/s41467-022-34540-x
|View full text |Cite
|
Sign up to set email alerts
|

Constraining surface properties of asteroid (162173) Ryugu from numerical simulations of Hayabusa2 mission impact experiment

Abstract: The Hayabusa2 mission impact experiment on asteroid Ryugu created an unexpectedly large crater. The associated regime of low-gravity, low-strength cratering remained largely unexplored so far, because these impact conditions cannot be re-created in laboratory experiments on Earth. Here we show that the target cohesion may be very low and the impact probably occurred in the transitional cratering regime, between strength and gravity. For such conditions, our numerical simulations are able to reproduce the outco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Overall, there is a need to verify the validity of 3D simulations of geologic rubble-pile targets against experiments. Currently, there is a paucity of 3D code validation studies for hypervelocity impacts into rubble-pile targets (Jutzi et al 2022;Ormö et al 2022). However, we note that a 3D validation study is ongoing for iSALE (Ormö et al 2023).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Overall, there is a need to verify the validity of 3D simulations of geologic rubble-pile targets against experiments. Currently, there is a paucity of 3D code validation studies for hypervelocity impacts into rubble-pile targets (Jutzi et al 2022;Ormö et al 2022). However, we note that a 3D validation study is ongoing for iSALE (Ormö et al 2023).…”
Section: Discussionmentioning
confidence: 91%
“…Previous missions to asteroids indicated that the surface structure and likely the substructure can vary significantly from one asteroid to another (Sullivan et al 2002;Miyamoto et al 2007; Barnouin et al 2019a;Rozitis et al 2020;Jutzi et al 2022). Generally, asteroids are categorized into three categories: solid objects made of strong, cohesive material; rubble piles containing strong pieces within a weaker matrix held together by self-gravity, small particles, and cohesion; and fractured shards consisting of a relatively strong body with large-scale fractures resulting from previous impact events (Bottke et al 2002).…”
Section: Introduction To the Dart Kinetic Impactor Testmentioning
confidence: 99%
See 1 more Smart Citation
“…These cohesion values are consistent with observations. On the low end, Bennu and Ryugu have surfaces on the order of 1 Pa cohesion (Jutzi et al 2022;Walsh et al 2022). Other observations show small rubble piles having global strengths of tens to hundreds Pa cohesion (Hirabayashi et al 2014;Rozitis et al 2014;Jewitt et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…their surfaces and potentially some strength at depth, so this implicit assumption by Sugiura & Kobayashi (2021) is not unreasonable (Barnouin et al 2019;Arakawa et al 2020;Jutzi et al 2022;Walsh et al 2022). However, recent work by Zhang et al (2022) demonstrates that rubble-pile failure mechanisms are highly sensitive to small changes in cohesion at a fixed friction angle and small changes in friction at constant cohesion, indicating that friction and cohesion cannot be combined into a single parameter and should be treated separately.…”
Section: Satellite Formation Via Mass Sheddingmentioning
confidence: 99%